Uji aktivitas antibakteri ekstrak etanol asam sunti terhadap bakteri Streptococcus mutans - Novika Utami; Haris Munandar Nasution; Rafita Yuniari; Yayuk Putri Rahayu (Journal of Pharmaceutical and Sciences, 2023)
Asam sunti is belimbing wuluh, which is processed into a special food additive from Aceh Province because it becomes dregs and interferes. Belimbing is processed into asam sunti for seasoning or additional dishes. Belimbing contains active compounds such as alkaloids, triterpenoids, saponins, tannins, and flavonoids. Because Belimbing has an antibacterial pharmacological effect, it has been shown to fight bacteria that cause dental caries. The main cause of dental caries is the activity of Streptococcus mutans bacteria. The researcher took the research problem regarding the test of the inhibitory power of asam sunti extract. They know the antibacterial activity of 96% ethanol extract. The method used in this study was an experimental method with independent variables, namely asam sunti simplicia and asam sunti concentration. The main variables were the secondary characteristics and the metabolite content of the asam sunti ethanol extract. The tests included inhibiting asam sunti's ethanol extract against bacteria. The results of plant identification showed that the antibacterial inhibition zone of the ethanol extract of asam sunti belimbing wuluh ethanol extract with a concentration of 20% (18.54) mm, 40% (20.79) mm, and concentration of 60% (21.48) mm including Thus is known that the concentration of ethanol extract of asam sunti Belimbing wuluh on 20%-60% is an effective concentration to inhibit Streptococcus mutans bacteria The concentration of the ethanol extract has very strong antibacterial powder, causing a large inhibition zone.